Minimum Overlap Difference in Dual Masting of GSM Network Design (Contemporary Mathematics, 2025)
Generally, cell radio systems are enormous scale engineering designs and consist of various technical entities. They represent significant financial investments and hence there is the need for scientific design approach in network designs. This calls for finding a minimum overlap difference using a dual masting. In the process of finding the minimum cardinality of the disk in the Global System for Mobile Communication (GSM) cover problem, the octagon-square Archimedean tessellate was deduced by manipulating a four cusps hypocycloid known as Astroid. Since this Archimedean tessellate is formed with two different polygons, it becomes a possible consideration for the dual signal masting. The overlap difference using the octagon-square Archimedean tessellate was found to be 11.73%. This is a 12.46% reduction of the hexagonal tessellation with overlap difference of 13.4%. It was found that for any octagon-square tessellate, the circumcircle radius of the octagon is always approximately 1.847 longer than that of the square and the apothem of the octagon is approximately 2.414 longer than that of the square.
Keywords: network; dual masting; minimum cardinality; radio systems; communication; overlap ratios; node points